Behavioral Insight : Review of the book of the same title by Hallsworth and Kirkman (Academic Journal of Internal Affairs, 2023)
Aim: The MIT Press Essential Knowledge series provides the reader with accessible, concise, yet interesting and completely up-to-date information. Till now, we have reviewed the following members of the series: Neuroplasticity (Németh, 2021a), Anticorruption (Németh, 2021b), Collaborative Society (Németh & Szabo, 2022), Critical Thinking (Németh, 2022b).Methodology: Each part was written by excellent experts on the subject, in a language understood by non-experts, too. In this way, the current research data and results in the field of each topic can be really used. Nowadays, it is not easy to find in the endless set of information obtainable on the World Wide Web those that essentially provide the fundamental knowledge on a particular topic (Tidor, 2020).Findings: Behavior insight examines the current and possible later relationship between conscious thinking and unconscious action processes. It also examines how to develop and use it ethically to the benefit of humanity.Value: The book presents the importance of conscious thinking and action, which is so far only known to scientists.
Keywords: behavior; manipulation; communication; behavioral history